An account of Anuran at crocker range National Park, Sabah - Ramlah, Zainudin; Lizanah, Wasly; Haidar, Ali (ARBEC, 2002)
The survey was conducted at three localities at Crocker Range National Park, Sabah. A total of 110 individuals and 18 species belonging to the family of Ranidae, Bufonidae, Microhylidae, Megophryidae and Rhacophoridae were identified. The family of Ranidae (44%) dominated the area with Rana kuhli being the most abundant (65 individuals). There was no significant difference in terms of species occurrence for both sites A and B (H=47.50, Mann-Whitney). Although more individuals were captured at Site A with a total of 73 individuals, Site B appeared to be more diverse in terms of species captured (H=0.829).